Salão Compartilhado: um estudo sobre a condução compartilhada entre dama e cavalheiro na dança de salão - MOREIRA, Aline de Nazaré de Paula (2019)
Historically, in the ballroom dances, the gentleman always led his lady, leaving her a passive role to follow the gentleman's movement, movement and musicality. However due to the cultural changes of women, this place is questioned, in this sense the present research turned, throughout its development, to a reflection on shared driving and more active ladies. Thus this study comes to problematizar: How does the shared conduction between lady and gentleman in the ballroom dance take place? This research intends to add other glances for this language in dance, that the two bodies can dialogue for the movement. The general objective of this work was to investigate the shared conduction of the hall dance between lady and gentleman. And the specific objectives of the research were: to analyze driving in the two-way dance and to weave approximations and differences in shared driving. The work by means of a qualitative autobiographical study expresses my experiences on this conduction, as well as record in my logbook, interview with practitioners of ballroom dancing, to result in the shared star. A contribution is expected in the discussion of the subject and that these proposals add up to the most dialogical understanding in dance to two, with free ladies in their body expression and sensitive gentlemen, open and who know that their ladies also get their space in the driving.